RITUAL MAPPACCI PADA UPACARA PERNIKAHAN DI KABUPATEN PINRANG - Alwi Usra Usman; Karta Jayadi; Abdul Rahman A. Sakka; Najamuddin Najamuddin (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2024)
This research aims to find out: (1) the procession of implementing mappacci in the Bugis tribe community, Pinrang Regency. (2) the symbolic meaning of the equipment used in the mappacci procession in the Bugis tribe community, Pinrang Regency. To achieve this goal, researchers used data collection techniques through observation, interviews and documentation. The data obtained from the research results were processed using qualitative analysis with a phenomenological approach to the Mappacci implementation procession in the Bugis Tribe community in Pinrang Regency and the symbolic meaning of the equipment used during the Mappacci implementation procession in the Bugis Tribe community in Pinrang Regency. Based on the results of this research, it shows that, (1) There are three stages in the process of implementing mappacci in the Bugis community of Pinrang Regency, the first stage is dio majeng and assa' demmeang, the second stage is barasanji and the last stage is mappacci. (2) There are nine pieces of equipment used during the mappacci procession in the Bugis community of Pinrang Regency, the first piece of equipment is henna leaves which symbolize purity, the second piece of equipment is a pillow which symbolizes comfort, the third piece of equipment is a silk sarong which symbolizes moral values, the fourth piece of equipment is banana leaves which symbolize continuity, the fifth equipment is rice which symbolizes development, the sixth equipment is candles which symbolize wisdom, the seventh equipment is jackfruit leaves which symbolize straightness, the eighth equipment is a pacci container which symbolizes unity and the last equipment is brown sugar and coconut which symbolize loyalty